Valorization of copper smelter slag through the recovery of metal values by a synergistic bioprocess system of bio‐flotation and bio‐leaching. Issue 1 (7th May 2022) - Behera, Sunil Kumar; Panda, Sandeep Kumar; Mulaba‐Bafubiandi, Antoine‐Floribert
Abstract: Slag sample generated as solid waste from a copper plant in Southern Africa contains strategically important base metals like copper, nickel and cobalt. X‐ray diffraction and X‐ray fluorescence analysis confirmed the presence of fayalite (Fe2 SiO4 ), silica (SiO2 ) and alumina (Al2 O3 ) as the major mineral phases in the slag sample. The presence of alumina and silicate minerals in copper slag are the major obstacles in the recovery of base metals in mineral processing industries. The copper slag may be hazardous if abandoned to the environment but it may be a valuable resource if the metal values can be recovered. Hence, the present study focused on the application of a bio‐surfactant extracted from Lactobacillus fermentum bacterium as a bio‐collector in the flotation of the slag sample to reduce its silica and alumina content. Subsequently, the slag sample was subjected to bio‐leaching by Acidithiobacillus ferrooxidans bacterium for recovery of the metal values. Flotation batch experiments were conducted in 1 L scale Denver flotation cell and during the process, about 37.90% of silica and 22.82% alumina were removed from the slag sample. The findings from this study further revealed the effectiveness of the bio‐surfactant‐assisted flotation process on the bio‐leaching of base metals from the slag sample. Flotation of silica and alumina from the slag improved bio‐leaching performance and recovered about 74.0% of copper, 60.0% of nickel and 33.4% cobalt in the bio‐leaching process conducted at laboratory scale.